Mutu Fisik, Kimia dan Sensori Kerupuk Varian Original, Ikan dan Susu Sapi Produksi UD. Bismillah - Arika Choiriyah (Fakultas Teknologi Pertanian, 2025)
Crackers are food products that contain high carbohydrate content. The addition of protein sources such as fish and cow's milk can improve nutrition and add flavor variants to crackers. The variety of flavors in crackers can increase consumer interest in consuming crackers. This research is a field experimental research at UD. Bismillah with a one-factor group randomized design, namely the cracker formula. F1 (original crackers), F2 (fish crackers), and F3 (milk crackers). The parameters analyzed included physical quality (texture, color, expandability and bulk density), chemical quality (water content, ash content, protein content, fat content, and carbohydrate content), sensory (hedonic and scoring), fish crackers had the crunchiest texture, the color of the three white crackers was slightly browned, milk crackers had the highest expandability and bulk density. the addition of fish and milk to the cracker dough decreased the water content and increased the ash, protein and fat content. The results of the sensory test of crackers using hedonic test and scoring showed that the fish variant of crackers was most preferred by panelists overall with a score of 5.60 (liked) with a description of a slightly brownish white color, strong fish aroma and taste and a very crunchy texture.
Entry oleh Arif 2026 Maret 16
Keywords: Crackers; Protein; Fish; Cow’s Milk